Knowledge and attitude towards COVID-19 among adult people in Bangladesh: evidence from an online survey - Md Shahjahan; M. Mazharul Islam; Md Kamrul Hossain; Md. Ruhul Amin; Mostafa Kamal; Mohammad Saiful Islam (Intelektual Pustaka Media Utama, 2023)
The objective of this study was to examine the levels and determinants of knowledge and attitudes toward COVID-19 among adult people in Bangladesh, using data from an online survey, conducted in May 2021. Descriptive and inferential statistical analysis were performed to extract findings from data. The survey covered 993 respondents. A high level (78.4%) of effective knowledge and positive attitude (78.6%) were observed among the Bangladeshi people. More than eighty percent of the respondents could correctly mention at least one important symptom, mode of transmission, and preventive measures of COVID-19. Good knowledge and positive attitudes were found to be significantly higher among males, living in Dhaka city, having a higher level of education, health professionals, and the wealthiest people. Knowledge about COVID-19 has significant association with positive attitude of people towards COVID-19. Despite the high level of knowledge and positive attitudes, there still prevails some misconceptions among a group of people, as one-third of the respondents opined that COVID-19 is a divine punishment and 13% were in favor of keeping it secrete if COVID-19 infection happen to them. The findings underscore the need for more educational program and behavior change communication (BCC) for the subgroups of the population that has been identified with poor knowledge and negative attitudes towards COVID-19.